Natural Antioxidant-Isoliquiritigenin Ameliorates Contractile Dysfunction of Hypoxic Cardiomyocytes via AMPK Signaling Pathway - Xiaoyu Zhang; Ping Zhu; Xiuying Zhang; Yina Ma; Wenguang Li; Ji-Mei Chen; Hui-Ming Guo; Richard Bucala; Jian Zhuang; Ji Li (Mediators of Inflammation)
Isoliquiritigenin (ISL), a simple chalcone-type flavonoid, is derived from licorice compounds and is mainly present in foods, beverages, and tobacco. Reactive oxygen species (ROS) is a critical factor involved in modulating cardiac stress response signaling during ischemia and reperfusion. We hypothesize that ISL as a natural antioxidant may protect heart against ischemic injury via modulating cellular redox status and regulating cardioprotective signaling pathways. The fluorescent probe H2DCFDA was used to measure the level of intracellular ROS. The glucose uptake was determined by 2-deoxy-D-glucose-3H accumulation. The IonOptix System measured the contractile function of isolated cardiomyocytes. The results demonstrated that ISL treatment markedly ameliorated cardiomyocytes contractile dysfunction caused by hypoxia. ISL significantly stimulated cardioprotective signaling, AMP-activated protein kinase (AMPK), and extracellular signal-regulated kinase (ERK) signaling pathways. The ROS fluorescent probe H2DCFDA determination indicated that ISL significantly reduced cardiac ROS level during hypoxia/reoxygenation. Moreover, ISL reduced the mitochondrial potential (Δψ) of isolated mouse cardiomyocytes. Taken together, ISL as a natural antioxidant demonstrated the cardioprotection against ischemic injury that may attribute to the activation of AMPK and ERK signaling pathways and balance of cellular redox status.